The role of alloantibodies against human platelet antigen‐15 in multiply platelet transfused patients. Issue 4 (22nd October 2013) - Matsuhashi, Mika; Tsuno, Nelson H.; Sone, Shinji; Mishima, Yuko; Nagura, Yutaka; Watanabe‐Okochi, Naoko; Ikeda, Toshiyuki; Kashiwase, Koichi; Fukuda, Shinya; Iriyama, Takayuki; Hyodo, Hironobu; Yamashita, Takahiro; et al.
<x xml:space="preserve">Abstract</x> Background Several studies have documented the role of antibodies against human platelet (PLT) antigen (HPA)‐15 in alloimmune‐mediated thrombocytopenia including neonatal alloimmune thrombocytopenia, PLT transfusion refractoriness (PTR), and posttransfusion purpura in Caucasian persons. However, the relevance of anti‐HPA‐15 in PTR among the Japanese population is still unclear. Study Design and Methods The sera of 305 multiply PLT transfused (MPT) patients, previously investigated for the presence of human leukocyte antigen (HLA) and HPA antibodies by mixed passive hemagglutination, were reexamined for the presence of HPA‐15 alloantibodies, using the monoclonal antibody–specific immobilization of PLT antigens (MAIPA) technique. Results Among the 305 MPT samples, antibodies against HPA‐15 alloantigen was detected in seven (2.3%), two (0.66%) being anti‐HPA‐15a and five (1.64%) being anti‐HPA‐15b. Additionally, one case of CD109 panreactive antibody was found (0.33%). Among them, one aplastic anemia patient with blood group O developed multispecific anti‐HLA and anti‐HPA‐15b alloantibody after MPTs. However, transfusion with HLA‐matched PLTs of blood group AB did not result in adequate PLT count increment. Analysis of the possible influence of immune anti‐A and anti‐B by the MAIPA assay resulted negative, indicating that anti‐HPA‐15b is responsible for the refractory state in this patient. Conclusion In this study, we found alloimmunization against HPA‐15a and ‐15b in Japanese populations and demonstrated the relevance of these antibodies in a patient with PTR.